2018
DOI: 10.1016/j.cpc.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The LS-STAG immersed boundary/cut-cell method for non-Newtonian flows in 3D extruded geometries

Abstract: The LS-STAG method is an immersed boundary/cut-cell method for viscous incompressible flows based on the staggered MAC arrangement for Cartesian grids, where the irregular boundary is sharply represented by its level-set function, results in a significant gain in computer resources (wall time, memory usage) compared to commercial body-fitted CFD codes. The 2D version of LS-STAG method is now well-established (Y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In addition, a number of specialized methods have been designed to achieve better than first order accuracy in the L ∞ norm. These include the immersed interface (e.g., [20,21,22,23] [24,25]), ghost fluid (e.g., [26,27,28,29]), cut-cell methods (e.g., [30,31,32,33]) and Voronoi interface (e.g., [34,35]) methods. These methods modify difference stencils near the domain boundary to account for the boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of specialized methods have been designed to achieve better than first order accuracy in the L ∞ norm. These include the immersed interface (e.g., [20,21,22,23] [24,25]), ghost fluid (e.g., [26,27,28,29]), cut-cell methods (e.g., [30,31,32,33]) and Voronoi interface (e.g., [34,35]) methods. These methods modify difference stencils near the domain boundary to account for the boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose is to assess the ability to compute accurately local heat flux at immersed boundaries, which is a sensible quantity since it involves the temperature gradient at the sold face of cut-cells. Once the DCM has been assessed on 2D flows, the DCM is applied to the Navier-Stokes equations in 3D-extruded geometries to enhance the discretization of isothermal incompressible flows computed with the LS-STAG method with 2-point discretization reported in [16]. First the spatial accuracy of the various variants of DCM is assessed on the test case of pure thermal conduction (Eq (1) with v = 0) between concentric cylinders of diameters r = R 1 and r = R 2 , where a temperature difference ∆T = T 2 − T 1 is applied.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, the Navier-Stokes computations in [16] reported that the use of the above two-point formulas diminishes the accuracy of the LS-STAG method, and that only a superlinear order of convergence was obtained. The reason is that, when α = 0, the face-normal gradient ∂T /∂x| e cannot be written as a function of T i,j and T i+1,j only, it also has a component tangential to the face also.…”
Section: Discretization Of Diffusion With the Diamond Cell Tech-niquesmentioning
confidence: 99%
See 2 more Smart Citations